Vulnerability Assessment of Climate Change in Vietnam: A Case Study of Binh Chanh District, Ho Chi Minh City - Truong, Dinh Duc; Dat, Tran Tho; Hang, Nguyen Dieu; Huan, Le Huy (Frontiers in Environmental Science, 2022)
Climate change poses additional obstacles to poverty eradication and social justice. Rising temperatures, abnormal rainfall increases, storms, floods and droughts become more frequent and severe, all phenomena in Vietnam. This is causing serious consequences for the livelihood security of the poor. Binh Chanh district (Ho Chi Minh city) is an area subject to servere risks of climate change in Mekong River Delta, Vietnam. Of which, low-income groups are the most vulnerable because their adaptive capacity is still limit and low. This paper uses the Livelihood Vulnerability Index (LVI) to assessing the level of vulnerability to climate change households and communes in Binh Chanh district. LVI includes 3 components: Exposure (E), Sensitivity (S) and Adaptive Capacity (AC) based on 23 indicators selected by reviewing literature and consulting with experts. The article also conducted surveys with 931 households in 16 administrative communes in Binh Chanh for primary data. Research results show that Tan Kien, An Qui Tay communes have highest level of vulnerability since they are areas with mainly low-lying terrain, contiguous location rivers; the people in these towns are also vulnerable groups because having not a stable source of income, skills and low education and experience in climate change adaptation. The study also proposes some solutions to improve the capacity to adapt to climate change of vulnerable communes, specifically: (1) creating a diversified livelihoods with stable incomes; (2) deploying a climate change adaptation model based on communities for ommunes adjacent to rivers; (3) implementing adaptive agriculture and improving social captial for vulnerable households; (4) building resettlement areas for households heavily affected by disasters; (5) raising awareness of low-income households to respond to natural hazards in the context of climate change.